The Role of Civic Identity in the Preferences of Civil and Political Forms of Social Activity in Russian Youth - Rail M. Shamionov (Peoples' Friendship University of Russia (RUDN University), 2020)
Civic identity is an important feature of a socialised person. It regulates numerous personal behavioural manifestations, e.g. commitment to the country, patriotism, willingness to participate in important processes related to democratic procedures, desire to realise values that are of paramount importance for adaptation and integration with other representatives of civil society. The aim of this research is to determine the role of civic identity in the preferences of civil and political forms of social activity among young people in provincial Russia. The study involved 305 people (35.4% men) aged 17 to 35 (M = 21.1; SD = 3.1). The study used a questionnaire aimed at determining the socio-demographic characteristics of the sample group, containing scales for assessing the degree of personal involvement in certain forms of social activity (R.M. Shamionov et al.), Civic Identity Scale (A.N. Tatarko), Self-Assessment of the Propensity for Extreme Risky Behavior Technique (the Russian version of M. Zuckermans Sensation Seeking Scale). The study revealed that the indicators of commitment to protest, radical-protest and subcultural activity are more homogeneous and less pronounced in comparison with the indicators of civic, political and socio-economic activity. As a result of the factor analysis, it was found that civic-political (civic, socio-economic and political) and subcultural-protest (subcultural, protest and radical-protest) forms of activity constitute two stable factors. As a result of structural modelling, it was shown that civic identity has a positive impact on social activity in the civil-political field and a negative impact on subcultural-protest activity. Seeking new experiences plays a positive role in subcultural-protest activity of young people, while the feeling of uncertainty undermines the manifestations of civic-political activity. The study also revealed an important role of socialisation conditions: the participation of parents in the public life of the country contributes to civic-political activity and the formation of civic identity of their children. Civic identity reduces the manifestation of the feeling of uncertainty and the search for new experiences among young people.